Accuracy Test of Lequesne Index for Radiology Imaging in Genu Osteoarthritis - Tunjung Radilustyasari; Rendra Leonas (Sriwijaya Journal of Surgery, 2019)
ABSTRACT Introduction. Osteoarthritis (OA) is a degenerative joint disease associated with damage to the joint cartilage and surrounding tissue. Osteoarthritis can affect all types of joints, but generally affects the knee, hip, hand, spine and leg joints. The main clinical features of OA are pain, stiffness and limited mobility. Lequesne index has the advantage of being easily and quickly used to assess the results of new drug research without objective evidence and can be used to follow OA for a long period of time. Methods. This study was a diagnostic study in the form of an accuracy test to assess sensitivity, specificity, positive predictive value and negative expected value. Results. 35 study subjects were obtained according to inclusion. Sensitivity value is 82.41%, specificity value is 71.4%, positive estimation value is 0.92% and negative estimation value is 0.50% and conformity value (kappa value) is 0.80. Conclusion. Lequesne index has a good value of conformity to the radiologic picture with a kappa value of 0.80.